Methodological quality of clinical practice guidelines with physical activity recommendations for people diagnosed with cancer: A systematic critical appraisal using the AGREE II tool. - Shirin M Shallwani; Judy King; Roanne Thomas; Odette Thevenot; Gino De Angelis; Ala' S Aburub; Lucie Brosseau (PLoS ONE, 2019)
Evidence suggests physical activity (PA) is beneficial for people diagnosed with cancer. Clinical practice guidelines provide specific recommendations based on available research and are useful in informing evidence-based practice and guiding future research. Little is known on the extent and quality of guidelines on PA targeted to the cancer population. The objectives of this systematic review were to: 1) identify recent clinical practice guidelines including PA or exercise recommendations for people with cancer and 2) critically appraise the methodological quality of the included guidelines. A systematic search of four electronic databases (MEDLINE, EMBASE, CINAHL and PEDro) and supplementary sources was conducted. Two reviewers independently scanned articles and selected guidelines for inclusion according to the following criteria: published in English, developed or updated in previous five years (January 2012-June 2017), published in peer-reviewed scientific journals, including ≥1 specific recommendation on PA or exercise, and relevant to adults diagnosed with cancer. Subsequently, two trained assessors independently appraised the included guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE) II tool. Average scores for six domains (scope and purpose; stakeholder involvement; rigour of development; clarity of presentation; applicability; and editorial independence) and overall quality were calculated. From the literature search, we identified 29 articles, representing 20 sets of guidelines meeting the selection criteria. The guidelines were applicable to the following cancer populations: general (n = 9), breast (n = 5), lung (n = 2), colorectal (n = 1), head and neck (n = 1), myeloma (n = 1) and prostate (n = 1). The guidelines were generally of moderate methodological quality (mean AGREE II overall quality score: 4.6/7, range 2.5-6). The area of lowest quality was in the domain of applicability (mean AGREE II quality domain score: 40%), whereas the strongest domains were related to scope and purpose (81%) and clarity of presentation (77%). Although there are limitations in the primary research informing the recommendations, guidelines of acceptable quality exist to direct stakeholders on targeted PA recommendations for a range of cancer populations. Improvement is needed in the applicability of guidelines to enhance their relevance and clinical use. Health professionals can play an important role in supporting people with cancer throughout the disease trajectory and benefit from access to well-developed and appropriate materials to interpret research knowledge on effective rehabilitation strategies, including PA.